A risk score to identify HIV-infected women most likely to become lost to follow-up in the postpartum period*. Issue 8 (2nd August 2016) - Bengtson, Angela M.; Chibwesha, Carla J.; Westreich, Daniel; Mubiana-Mbewe, Mwangelwa; Chi, Benjamin H.; Miller, William C.; Mapani, Muntanga; Pence, Brian W; Musonda, Patrick; Stringer, Jeffrey SA; Pettifor, Audrey
ABSTRACT: Access to lifelong combination antiretroviral therapy (cART) is expanding among HIV-infected pregnant and breastfeeding women throughout sub-Saharan Africa (SSA). For this strategy to meaningfully improve maternal HIV outcomes, retention in HIV care is essential. We developed a risk score to identify women with high likelihood of loss to follow-up (LTFU) at 6 months postpartum from HIV care, using data from public health facilities in Lusaka, Zambia. LTFU was defined as not presenting for HIV care within 60 days of the last scheduled appointment. We used logistic regression to assess demographic, obstetric and HIV predictors of LTFU and to develop a simple risk score. Sensitivity and specificity were assessed at each risk score cut-point. Among 2029 pregnant women initiating cART between 2009 and 2011, 507 (25%) were LTFU by 6 months postpartum. Parity, education, employment status, WHO clinical stage, duration of cART during pregnancy and number of antenatal care visits were associated with LTFU ( p -value < .10). A risk score cut-point of 11 (42nd percentile) had 85% sensitivity (95% CI 82%, 88%) and 22% specificity (95% CI 20%, 24%) to detect women LTFU and would exclude 20% of women from a retention intervention. A risk score cut-point of 18 (69th percentile) identified the 23% of women with the highest probability of LTFU and had sensitivity 32% (95% CI 28%, 36%) and specificity 80% (95% CI 78%, 82%). A risk score approach may be useful to triage a subset of women most likely to be LTFU for targeted retention interventions.